Didactic Foundations and Educational Effects of Individually Planned Teaching - Ljiljana S. Jerković (University of Belgrade, Teacher Education Faculty, 2020)
Individually planned instruction is a system of individualized instruction, whose didactic foundations have not yet been fully elucidated. In actuality, there have been no attempts by local researchers or educators to validate the educational effects of this type of instruction as provided in the local context, special in terms of organization of instruction, the staff providing instruction, and material and technical circumstances and conditions. The aim of the theoretical part of the research was to develop and operationalize the didactic foundations of individually planned instruction. The aim of the empirical part of the research was to determine the educational effects of individually planned instruction. Given the nature and complexity of the problem researched, both a quantitative approach and a qualitative approach were applied. Experimental action research was carried out on a sample of 150 students, with 32 strong experimental semple, of which 16 participants were the experimental group and the other 16 the control group. The experimental group received instruction in the Serbian (native) language and mathematics following didactically founded and individually planned classes for a year, during which they achieved results that were more statistically significant as relative to their initial situation and the achievement of the students in the control group, who were taught in the traditional, non-individualized way. The research specified the range of possibilities for the dissemination and productive implementation of the experimentally validated individually planned instruction. It also raised issues that merit attention in future research.